Ketika Hukum Abai: Kritik terhadap Putusan Pengadilan dan Pengawasan OJK dalam Kasus Jiwasraya - M. Reyhan Aldabena; Reza Kautsar Kusumahpraja; Achmad Jaelani; Andi Heridah (Jurnal Litigasi Amsir, 2026)
This study examines the development of national law as a dynamic instrument for achieving social welfare, with particular emphasis on civil law disputes in the insurance sector, especially those arising between creditors and debtors. It analyzes the legal construction of insolvency and its distinction from bankruptcy within Indonesian law, highlighting that insolvency does not automatically lead to bankruptcy but reflects a financial imbalance where liabilities exceed assets. Focusing on the case of PT Asuransi Jiwasraya (Persero), this normative legal research employs statutory, case, and conceptual approaches to assess the failure to apply the principles of good faith and strict liability in resolving insurance disputes. The findings reveal that despite clear indications of insolvency, mismanagement, and corruption, judicial considerations inadequately recognized prima facie evidence and public facts, resulting in suboptimal legal protection for policyholders. Furthermore, the study underscores the weakness of regulatory oversight by the Financial Services Authority (OJK), which failed to effectively prevent and respond to the company’s financial collapse. The research concludes that strengthening the application of strict liability, enhancing judicial sensitivity to evidentiary standards, and improving regulatory supervision are essential to greater legal certainty and protection for insurance consumers